Survival of women with cancers of breast and genital organs in Europe 1999–2007: Results of the EUROCARE-5 study. Issue 15 (October 2015) - ; Hackl, M.; Zielonke, N.; Oberaigner, W.; Van Eycken, E.; Henau, K.; Valerianova, Z.; Dimitrova, N.; Sekerija, M.; Zvolský, M.; Dušek, L.; Storm, H.; et al.
Abstract: Background: Survival differences across Europe for patients with cancers of breast, uterus, cervix, ovary, vagina and vulva have been documented by previous EUROCARE studies. In the present EUROCARE-5 study we update survival estimates and investigate changes in country-specific and over time survival, discussing their relationship with incidence and mortality dynamics for cancers for which organised screening programs are ongoing. Methods: We analysed cases archived in over 80 population-based cancer registries in 29 countries grouped into five European regions. We used the cohort approach to estimate 5-year relative survival (RS) for adult (⩾15 years) women diagnosed 2000–2007, by age, country and region; and the period approach to estimate time trends (1999–2007) in RS for breast and cervical cancers. Results: In 2000–2007, 5-year RS was 57% overall, 82% for women diagnosed with breast, 76% with corpus uteri, 62% with cervical, 38% with ovarian, 40% with vaginal and 62% with vulvar cancer. Survival was low for patients resident in Eastern Europe (34% ovary–74% breast) and Ireland and the United Kingdom [Ireland/UK] (31–79%) and high for those resident in Northern Europe (41–85%) except Denmark. Survival decreased with advancing age: markedly for women with ovarian (71% 15–44 years; 20% ⩾75 years) and breast (86%; 72%) cancers. Survival for patients with breast and cervical cancers increased from 1999–2001 to 2005–2007, remarkably for those resident in countries with initially low survival. Conclusions: Despite increases over time, survival for women's cancers remained poor in Eastern Europe, likely due to advanced stage at diagnosis and/or suboptimum access to adequate care. Low survival for women living in Ireland/UK and Denmark could indicate late detection, possibly related also to referral delay. Poor survival for ovarian cancer across the continent and over time suggests the need for a major research effort to improve prognosis for this common cancer.